2013
DOI: 10.1080/19393210.2013.812148
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins in selected Thai commodities

Abstract: Aflatoxin (AF) B1, B2, G1 and G2 were determined in 120 samples of selected Thai commodities including unpolished rice, unpolished glutinous rice, chilli powder, whole dried chilli pods and raw peanut. The mean concentrations of the total AFs for analysed samples were 0.16, 25.43, 14.18, 6.62 and 1.43 µg kg(-1) with positive incidences of 4%, 20%, 97%, 37% and 30%, respectively. Quantitative analysis was performed using HPLC equipped with post-column derivatisation and fluorescence detection. Sample clean-up w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Anti-fungal chemicals, dichloran and rose bengal were inactive in depressing the growth of these fungi in the sample. Aflatoxin contamination in Thai commodities has been reported by several studies [2,8]. In this study, we also detected AFB 1 in a sample of Luem phua rice in the Pathum Thani region, close to Bangkok.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Anti-fungal chemicals, dichloran and rose bengal were inactive in depressing the growth of these fungi in the sample. Aflatoxin contamination in Thai commodities has been reported by several studies [2,8]. In this study, we also detected AFB 1 in a sample of Luem phua rice in the Pathum Thani region, close to Bangkok.…”
Section: Discussionsupporting
confidence: 78%
“…In Thailand, the major mycotoxins associated with cancer risk found in market commodities are aflatoxin (AF) B 1 and other aflatoxins [1]. AFB 1 is a strong class I carcinogen according to the International Agency for Research on Cancer, and several studies have reported rice contaminated with AFB 1 and other aflatoxins among Thai commodities [2,3,4]. In the postharvest condition, harvested rice grains may be damaged in several ways, such as fungal invasion, mycotoxin contamination, physicochemical changes, and insect activity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, fluorescent detection sensitivity of AFB 1 requires a conversion to more highly fluorescent derivatives (AFB 2a ). Several derivatization methods are available, including precolumn treatment with trifluoroacetic acid or postcolumn derivatization with pyridinium hydrobromide [ 2 , 17 ]. With an existence instrument, the method used the precolumn derivatization throughout the quantitative determinations.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies in other countries, high prevalence of natural contamination of CP with AFB 1 was reported. For example, 77% in Sri Lankan CP 12) , 100% (10 out of 10) in Iranian red pepper 13) , and 96.7% (29 out of 30) in Thailand CP 14) . In most cases, besides AFB 1 , AFB 2 was sometimes simultaneously detected, while AFG 1 nor AFG 2 was not detected, as in the case of this study.…”
Section: Resultsmentioning
confidence: 99%